White Place, general view of a private residence, Brookline, Massachusetts, 21 of 21. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a building in the White Place area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: Brookline, MA 10/78 White Place Brookline Walking Tours.; Binder Number 4. Pocket Number: 18.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1978-10.; Apply to the DCA for access to the physical slides.